1991
DOI: 10.1021/jf00002a013
|View full text |Cite
|
Sign up to set email alerts
|

Low-field nuclear magnetic resonance relaxation study of the thermal denaturation of transferrins

Abstract: The NMR method previously described by Lambelet et al. (J. Dairy Res. 1989,56,211-222) has been evaluated for the investigation of thermal and acid denaturation of transferrins in aqueous solution.Heating an apoovotransferrin or an apolactoferrin solution resulted in a slight increase in T1-l and an important increase in T2-1 relaxation rates within the denaturation range. The same treatment applied to corresponding iron-saturated proteins resulted in a decrease in these parameters due to modifications of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Here, the transverse magnetization relaxation time constant, T 2 , is sensitive to slow molecular motions of water. The denatured and cross-linked proteins caused a significant decrease in the water proton mobility and thereby a decrease in the water proton T 2 (37), which was observed as a darker region in Figure 4. Therefore, MRI provided an alternative, independent, and direct method of measuring protein coagulation (38), and was utilized to verify the uniformity of these in vitro and in vivo thermal lesions.…”
Section: Methodsmentioning
confidence: 95%
“…Here, the transverse magnetization relaxation time constant, T 2 , is sensitive to slow molecular motions of water. The denatured and cross-linked proteins caused a significant decrease in the water proton mobility and thereby a decrease in the water proton T 2 (37), which was observed as a darker region in Figure 4. Therefore, MRI provided an alternative, independent, and direct method of measuring protein coagulation (38), and was utilized to verify the uniformity of these in vitro and in vivo thermal lesions.…”
Section: Methodsmentioning
confidence: 95%
“…Most published T g data of food materials were obtained using differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA) and dynamic mechanical thermal analysis (DMTA) Karel, 1990, 1991;Lambelet et al, 1991;Kalichevsky et al, 1992ab), which measure thermal or thermomechanical characteristics accompanying the transitions. However, these methods are limited to specific forms and sizes of the test specimens.…”
Section: Introductionmentioning
confidence: 99%
“…In MRI, the transverse magnetization relaxation time constant, T 2 , is sensitive to slow molecular motions of water. The denatured and cross-linked proteins caused a significant decrease in the water proton mobility and thereby a decrease in the water proton T 2 (Lambelet et al, 1991), which was observed as a darker region in Fig. 2.…”
Section: (A)] and Then A Spiral Sidewall [3 MM In Thicknessmentioning
confidence: 89%